2015
DOI: 10.1186/s12864-015-2255-0
|View full text |Cite
|
Sign up to set email alerts
|

Population genomics of pearl millet (Pennisetum glaucum (L.) R. Br.): Comparative analysis of global accessions and Senegalese landraces

Abstract: BackgroundPearl millet is a staple food for people in arid and semi-arid regions of Africa and South Asia due to its high drought tolerance and nutritional qualities. A better understanding of the genomic diversity and population structure of pearl millet germplasm is needed to support germplasm conservation and genetic improvement of this crop. Here we characterized two pearl millet diversity panels, (i) a set of global accessions from Africa, Asia, and the America, and (ii) a collection of landraces from mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 78 publications
2
73
2
Order By: Relevance
“…Recently, phenotyping (Sy et al, 2015) and genotyping by sequencing (Hu et al, 2015) studies were carried out on a set of Senegalese pearl millet landraces. Sampling was restricted to only one agro-ecological area of Senegal, the Groundnut Basin, and included only nine so-called intermediate-flowering landraces (flower between 75 to 100 days after sowing).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, phenotyping (Sy et al, 2015) and genotyping by sequencing (Hu et al, 2015) studies were carried out on a set of Senegalese pearl millet landraces. Sampling was restricted to only one agro-ecological area of Senegal, the Groundnut Basin, and included only nine so-called intermediate-flowering landraces (flower between 75 to 100 days after sowing).…”
Section: Introductionmentioning
confidence: 99%
“…Based on phenology, head architecture and grain color, these accessions were classified into three cultivar groups, indicating a morphological diversity between early flowering landraces (Sy et al, 2015). Using 83,875 single nucleotide polymorphisms (SNPs) on the same set of accessions in addition to 252 global accessions, a higher genetic diversity was observed in Senegal accessions compared to millet accessions in India, South and Western Africa (Hu et al, 2015). Any local structure was evidenced, therefore studies of loci that control the cycle length would be necessary to assess more accurately the evolution of cultivated millet varieties (Dussert et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Sehgal et al (2012) used available pearl millet ESTs and developed 75 SNP and CISP markers and demonstrated their use in identifying candidate genes underlying a major DT-QTL using four genotypes namely, H 77/833-2, PRLT 2/89-33, ICMR 01029 and ICMR 01004, representing parents of two mapping populations. There is another recent research on identification of 83,875 SNP markers using genotyping by sequencing (GBS) of PstI-MspI reduced representation libraries in 500 genotypes of pearl millet, comprised of 252 global accessions and 248 Senegalese landraces, which exhibited high genetic diversity relative to other genotypes of Africa and Asia (Hu et al, 2015). Further ISSR-derived sequence characterized amplified region (SCAR) markers were developed to screen out polymorphism in a pair of pearl millet genotypes ICMR-01007 (P1) and ICMR-01004 (P2) and their population for downy mildew resistance.…”
Section: Genetic and Genomic Resourcesmentioning
confidence: 99%
“…With a closer phylogenetic relationship, more shared synteny and no complicated duplication history, S. viridis is generally a better reference than sorghum or maize for both purposes. For example, Hu et al (2015) examined a diverse panel of pearl millet and showed that shared markers and size of syntenic regions between Setaria and pearl millet is more than double of those between sorghum and pearl millet. In addition, S. viridis allelic variation can be directly introgressed into foxtail millet through interspecific crosses.…”
Section: Advances Of Forward Genetics In Setaria and Other Milletsmentioning
confidence: 99%